Study of Head Loss in Rapid Filtration with four River Sands - Agbo, Komitse Edoh; AyitÃ©, Yawovi M. X. Dany; Pachoukova, Irina (Salehan Institute of Higher Education, 2021)
In this work, we studied the filtration behavior, with regard to the head loss, of four calibrated Togo Rivers sands compared to that of a reference filter sand imported from Europe. The objective is to determine the suitability of local rivers sands as filter sands for water treatment plants. The sands were successively loaded into a filtration pilot and subjected, during at least 20 hours, to the filtration of water whose turbidity was maintained at around 20 NTU. The results show that the average deviations of the head loss profiles as a function of depth, calculated in relation to the head loss recorded on the reference sand, at the same filtration time t=20h, are small and vary from 2 cm to 8 cm.Â In the same way, the curves of the head loss as a function of time are quite close to the one observed for the reference sand. Examination of the clogging front after 20 hours of filtration reveals that the progression is either the same or greater and reached 20 cm in depth at the same time. This study can be extended to other rivers sand samples and by varying the turbidity and the filtration rate.Â Doi: 10.28991/cej-2021-03091682 Full Text: PDF